Ensino informatizado de leitura e de escrita a uma turma da Educação de Jovens e Adultos - Silva, Érika Rímoli Mota da (2020)
Reading and Writing abilities are important for society as well the individual, however, the number of people with intellectual disability and illiterate elderly is still quite expressive. The Youth and Adult Education (EJA) is an education modality directed to people who could not complete their schooling in regular time, serving young people, adults, and the elderly. Considering this context of school, this study aimed to evaluate the effects of the application of the teaching modules of the Learning to Read and Write in Small Steps (ALEPP) curriculum with an EJA class. The ALEPP curriculum has three modules. Module 1 teaches simple and regular words of the Portuguese language, composed by consonant-vowel (for example, bolo - cake, salada - salad, fivela - buckle); Module 2 teaches words with irregularities of the Portuguese language (for example, gelo - ice, galinha – chicken, barco - boat, testa - forehead, garrafa - bottle, among others); and Module 3 aims at comprehension of short texts. Nine students participated in the study, one 19 years old young person with intellectual disability, six adults with intellectual disability between 21 and 40 years old, one adult 58 years old, and one elderly woman 69 years old. From the initial assessment of reading and writing skills, the participants were directed to the ALEPP teaching modules. The application of the Module occurred collectively, on average three days a week, with all students in a classroom provided by the school. Intermediate assessments of reading and writing skills were conducted before and after school recess periods, upon completion of the Module (post-test) and maintenance. The experimental activities were conducted in the presence of the researcher, the regular classroom teacher, and undergraduate interns. The results showed that students benefited from the teaching modules of the ALEPP curriculum, showing improvement in the performance of skills assessed, especially in reading and writing words. The participants who completed Module 1 presented maintenance of the performances in the evaluation that occurred from one to five months after the post-test. Six participants performed Module 2, one of them finished the 20 teaching units (irregularities of Portuguese language), and the other five completed different quantities of units. The results showed that the participants needed a number of distinct repetitions of four teaching steps of each unit; in general, the second teaching step had the highest number of repetitions and the fourth step had the lowest. The participant who performed Module 3 showed an improvement in the comprehension of texts with reading repetitions of the same book. Overall, the results showed that the ALEPP curriculum as a supplementary and complementary resource to the classroom can be a tool to enhance the learning of reading and writing by EJA students, creating teaching and motivational conditions for this audience. It is important to emphasize that the application in collective form was important to attend all students in the class and for the development of collaborative work between researcher, teachers, and interns. Future studies should investigate the use of the ALEPP curriculum by teachers with students with intellectual disabilities, adults and elderly as a complementary and supplementary resource.